Computational linguistic systematization of a lexicon from the ibitinga embroidery industry conceptual domain - Marcellino, Erasmo Roberto [UNESP]; Dias Da Silva, Bento Carlos Da [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2010)
This work discusses a proposition for organizing the lexical items from the conceptual domain labeled THE EMBROIDERY INDUSTRY OF IBITINGA in terms of a natural ontology. It also aims to establish the alignment between this ontology and the bases WordNet.Pr and WordNet.Br. © 2009 IEEE.
Keywords: Embroidery industry; Lexical items; Computational linguistics; Textile industry; Textile printing; Ontology